Hewn and cleft from this rock: meditation at the PreCambrian contact - Rolston, Holmes, 1932-2025, author; Gordon and Breach Science Publishers, publisher (Colorado State University. Libraries, 1971)
Encounter with the Precambrian contact exposed at Pardee Point in Doe River Gorge, East Tennessee, brings reflections about human origins, evolving and cleft from ancient rocks. Geochemistry has its sequel in biochemistry. The hiker crosses that fossil sequence recorded in the strata. A discontinuity is crossed with the coming of humans: A sheriff crossing the contact in search of moonshiners. The rocks are a sacrament that overlie a Presence.
Keywords: geology; precambrian terrain; precambrian contact; meditations; Homo faber; Homo moralis; Homo admirans: Tennessee